Investigation on the Effect of Butyl Acrylate (nBA) to Improve the Toughness Properties of Methacrylate-Based Waterproofing Adhesive Material (MMA) for the Steel Bridge Deck - Mengya Zhang (Advances in Materials Science and Engineering)
Waterproof adhesion materials (WAL) for steel bridge decks should have comprehensive strong bonding capabilities to steel substrates/pavement layers, water resistance, and persistence to harsh conditions. Methacrylate-based adhesive (MMA), as a typical WAL material for steel bridge decks, lacks sufficient flexibility and diverse compatibility. In this article, flexible, stabile at high temperature, and well-bonded poly (methyl methacrylate)/n-butyl acrylate copolymer [poly(MMA-r-nBA)] coatings were developed with toughening as a breakthrough point. The above properties are obtained by forming an interpenetrating network through interchain van der Waals forces. In addition to the flexibility provided by the long-chain structure of n-butyl acrylate, its unique molecular structure allows it to improve the high-temperature stability and lower the glass transition temperature of MMA. Due to the reduced glass transition temperature, it can also be matched to various pavement layers. Thus, the poly(MMA-r-nBA) composite polymer coatings can be applied to steel bridge decks that require long-term service in various conditions.